Interdecadal Changes in the Freeze Depth and Period of Frozen Soil on the Three Rivers Source Region in China from 1960 to 2014. (19th March 2017) - Luo, Siqiong; Fang, Xuewei; Lyu, Shihua; Jiang, Qi; Wang, Jingyuan
Abstract : On the basis of observed soil freeze depth data from 14 meteorological stations on the Three Rivers Source Region (TRSR) in China during 1960 to 2014, trends in the freeze depth, first date, last date, and duration of frozen soil were analyzed, together with other meteorological variables, such as air temperature, snow depth, and precipitation, observed at the same locations. The results showed the following. (1) A continuous, accelerated decreasing trend in freeze depth appeared in the TRSR during the 1985–2014 and 2000–2014 periods, compared with that during the 1960–2014 period. (2) The freeze first date had been delayed and the freeze last date had been advanced significantly. The advanced trends in freeze last date were more significant than the delayed trends in freeze first date. The freeze duration also experienced an accelerated decrease. (3) The freeze depth and period were strongly affected by air temperature, thawing index, and soil moisture (precipitation), but not by snow. The freeze depth, freeze first date, freeze last date, and duration also influenced each other. (4) These decreasing trends in freeze depth and duration are expected to continue given the increasing trends in air temperature and precipitation in this region.